Evaluación de la calidad de cursos virtuales MOOC por docentes de las instituciones educativas públicas de nivel inicial de Saposoa, San Martín 2021 - Sevillano Bazan, Mayra Patricia (2021)
The present study has been carried out with the purpose of describing the level of evaluation of the quality of the virtual Mooc courses carried out by the teachers of the public educational institutions of initial level of Saposoa in the San Martín region during 2021. The type of descriptive research supported by a cross-sectional, field design and attending only to a single variable was proposed as a methodology. The study population considered 23 teachers who are working in 4 educational institutions of initial level in Saposoa, the sample was census for convenience. In order to obtain the data, the survey technique and a questionnaire were used, which was previously validated by experts. The main conclusion of the study is that 4.3% of participating teachers rate the quality of the Mooc virtual courses they have received to date as a low level, 82.6% of them place it at an intermediate level and only 13.1% believe that virtual courses are at a high level.